A Common Fixed Point Theorem for Pairs of Mappings in Cone Metric Spaces - Sahin, Ilker; Telci, Mustafa (CUBO, A Mathematical Journal, 2014)
In this paper, we present a common fixed point theorem in complete cone metric spaces which is a generalization of the theorem in [6]. This result also generalizes some theorems given in [4] and [9].